PEMBERDAYAAN UMKM MELALUI PENDEKATAN ABCD BERBASIS LITERASI BILINGUAL DAN DIGITAL MARKETING UNTUK MENINGKATKAN DAYA SAING PRODUK - Nova Kristian; Ringgi Candraning Prawerti; Susilowati, Eni; Yunesia Pramesthi; Anindita Badianti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tulungagung, 2026)
This study aims to empower Micro, Small, and Medium Enterprises (MSMEs) through an Asset-Based Community Development (ABCD) approach grounded in bilingual literacy and digital marketing to enhance product competitiveness. The phenomenon examined is the limited ability of MSME actors to develop communicative and effective promotional content in both Bahasa Indonesia and English, as well as the suboptimal utilization of digital marketing strategies. This research employs the ABCD approach, consisting of the stages of discovery, dream, design, and destiny, which emphasize active community participation in identifying and developing local assets. Data were collected through semi-structured interviews, participatory observation, and documentation involving selected MSME actors using purposive sampling. The findings reveal three main outcomes: the improvement of bilingual literacy in marketing communication, the optimization of digital marketing as a promotional medium, and the strengthening of MSME actors’ capacity and self-confidence. The integration of language literacy and marketing strategies proved effective in generating more persuasive promotional content and increasing consumer engagement. These findings indicate that asset-based empowerment combined with communicative approaches and digital technology can produce a significant impact on business development. The study concludes that the ABCD approach based on bilingual literacy and digital marketing is effective in sustainably enhancing MSME competitiveness. This research contributes theoretically by offering an interdisciplinary integration framework in community empowerment studies and practically by proposing an applicable training model. Future research is recommended to examine the long-term impact on business performance and to expand the implementation across various MSME sectors.